Hubungan antara Pengobatan Komplementer dengan Kualitas Hidup pada Pasien Diabetes Mellitus - Nur Yusrin Husnati; Anita Kustanti; Heny Suseani Pangastuti (PSIK FKKMK UGM, 2017)
Background: Diabetes mellitus is a chronic disease that can affect physical, psychological, social and spiritual functional activity that requires special approach and treatment to improve patient's quality of life. One of treatments to improve quality of life is therapy management with alternative and complementary medicine.Objective: To determine the correlation between the use of complementary medicine with the quality of life among diabetes mellitus patients.Methods: This study used an analytic survey with cross-sectional design. Respondents involved in this study were 120 respondent diabetes mellitus patients in Yogyakarta city from August to September 2017 with purposive sampling technique. This study used Diabetes Quality of Life Clinical Trial Questionnaire-Revised Parameter (DQLCTQ-R) questionnaire to measure quality of life among diabetes mellitus patients. Researchers also included questions about the use of complementary therapies to measure the use of complementary therapies. Contingency coefficient correlation test was used to analyze the data statistically.Results: Most patients did not use complementary medicine (53,3%). Most users of complementary and non-complementary medicine had the same high quality of life (60,71% and 56,25%). The correlation test values between complementary medicine and quality of life in patients with diabetes mellitus showed p value = 0,621 (p> 0,05) and r = 0,045.Conclusion: There was no significant correlation between the uses of complementary medicine with quality of life among diabetes mellitus patients.ABSTRAKLatar belakang: Diabetes mellitus merupakan penyakit kronis yang dapat mempengaruhi aktivitas fungsional fisik, psikologis, sosial dan spiritual yang memerlukan pendekatan dan pengobatan khusus untuk meningkatkan kualitas hidup pasien. Salah satu perawatan untuk meningkatkan kualitas hidup adalah manajemen terapi dengan pengobatan komplementer.Tujuan: Mengetahui hubungan antarapengobatan komplementer dengan kualitas hidup pasien diabetes mellitus.Metode: Penelitian ini menggunakan survei analitik dengan desain cross-sectional. Responden yang dilibatkan dalam penelitian ini 120 pasien diabetes mellitus di Kota Yogyakarta dari bulan Agustus sampai September 2017 yang diambil dengan teknik purposive sampling. Penelitian ini menggunakan kuesioner Diabetes Quality of Life Clinical Trial Questionnare-Revised Parameter (DQLCTQ-R) untuk megukur kualitas hidup pasien diabetes mellitus. Peneliti juga mencantumkan pertanyaan tentang penggunaan terapi komplementeruntuk mengukur penggunaan terapi komplementer. Uji korelasi koefisien kontingensi digunakan untuk menganalisis secara statistik.Hasil: Mayoritas pasien tidak menggunakan pengobatan komplementer (53,3%). Mayoritas pengguna pengobatan komplementer dan bukan pengguna pengobatan komplementer sama-sama memiliki kualitas hidup yang tinggi (60,71% dan 56,25%). Nilai uji korelasi antara pengobatan komplementer dengan kualitas hidup pada pasien diabetes mellitus menunjukkan nilai p = 0,621 (p> 0,05) dan r = 0,045.Kesimpulan:Tidak ada hubungan yang signifikan antarapengobatan komplementer dengan kualitas hidup pada pasien diabetes mellitus.